Children’s oral communication in english class activities: an exploratory study (2006)
It is important that teachers fully equip students with the skills needed to communicate effectively in the target language so that they can share and exchange their ideas, feelings, opinions, etc. This article reports on a study aimed at examining the development of children’s oral communication in English and the way in which the activities and the teacher’s roles created or expanded students’ opportunities for learning. Data collection techniques included field notes, audio and video recordings and two interviews to the teacher. The study revealed that children’s oral production was possible thanks to the teacher’s efforts to provide children with topics and activities closely related to the students’ particular interests and needs. Likewise, the teacher created an appropriate learning environment in which children were challenged to use English in meaningful ways. Key words: Oral communication, young learners, teaching English, children, teacher’s roles Es importante que los maestros faciliten a sus estudiantes las habilidades necesarias para comunicarse efectivamente en la lengua extranjera, de tal forma que puedan compartir e intercambiar sus ideas, sentimientos, opiniones, etc. Este artículo reporta sobre un estudio encaminado a examinar el desarrollo de la comunicación oral de los niños en inglés y de la forma en que las actividades y los roles del profesor crearon y ampliaron las oportunidades de aprendizaje de los niños. Las técnicas de recolección de datos incluyeron notas de campo, grabaciones de audio y video y dos entrevistas a la profesora participante. El estudio reveló que la producción oral de los niños fue posible gracias a los esfuerzos de la profesora para brindarles temas y actividades estrechamente relacionados con sus intereses y necesidades particulares. Así mismo, la profesora creó un ambiente de aprendizaje apropiado en el cual los niños usaron el inglés de manera significativa. Palabras claves: Comunicación oral en niños, enseñanza del inglés a niños, roles del profesor